Mediation with Incomplete Information: Approaches to Suggest Potential Agreements - Sarabando, Paula (2015)
In bilateral Negotiation Analysis, the literature often considers the case of complete information. In this context, since the negotiators know the value functions of both parties, it is not difficult to calculate the Pareto efficient solutions for the negotiation. Thus rational negotiators can reach agreement on this frontier. However, these approaches are not applied in practicewhen complete information is not available. The research question of ourwork is “It is possible to help negotiators achieving an efficient solution in the absence of complete information regarding the different parameters of the model?”. We propose to derive incomplete information about the preferences of negotiators from the statements they make and the offers they exchange during the negotiation process. We present and discuss three approaches that use this information in order to help a mediator proposing a better solution than the compromise the negotiators have reached or are close to reach.